2018
DOI: 10.1021/acs.macromol.8b01060
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Dynamics of Pyrene Incorporated into Poly(substituted methylene)s: Effects of Dense Packing of Pyrenes on Excimer Formation

Abstract: The excited-state dynamics of pyrene incorporated into poly­(substituted methylene)­s is investigated by picosecond time-resolved fluorescence spectroscopy and femtosecond time-resolved near-IR absorption spectroscopy in the 900–1400 nm region. The pyrene rings in poly­(substituted methylene)­s are photoexcited to the monomer excited state immediately after UV irradiation, followed by prompt excimer formation with time constants of a few picoseconds to a few hundred picoseconds. The excimer formation in poly­(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…These polymers are generally prepared via the polymerization of vinyl monomers. An alternating method is the polymerization of one-carbon (C1) units such as isocyanide, dimethylsulfoxonium methylide, and diazocarbonyl compounds. The last compound is of particular interest because it can afford well-defined C–C main-chain polymers bearing polar substituents at every main-chain carbon, which cannot be accessed by Ziegler–Natta catalysts. , Thus, the diazoacetate polymerization seems to be an attractive route to prepare C–C main-chain functional polymers. It can be argued that the radical polymerization of dialkyl fumarates or maleates can also produce polymers with similar structures. , However, the living/controlled polymerizations of these monomers have never been attained so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These polymers are generally prepared via the polymerization of vinyl monomers. An alternating method is the polymerization of one-carbon (C1) units such as isocyanide, dimethylsulfoxonium methylide, and diazocarbonyl compounds. The last compound is of particular interest because it can afford well-defined C–C main-chain polymers bearing polar substituents at every main-chain carbon, which cannot be accessed by Ziegler–Natta catalysts. , Thus, the diazoacetate polymerization seems to be an attractive route to prepare C–C main-chain functional polymers. It can be argued that the radical polymerization of dialkyl fumarates or maleates can also produce polymers with similar structures. , However, the living/controlled polymerizations of these monomers have never been attained so far.…”
Section: Introductionmentioning
confidence: 99%
“…1−5 The last compound is of particular interest because it can afford well-defined C−C main-chain polymers bearing polar substituents at every mainchain carbon, which cannot be accessed by Ziegler−Natta catalysts. 6,7 Thus, the diazoacetate polymerization seems to be an attractive route to prepare C−C main-chain functional polymers. It can be argued that the radical polymerization of dialkyl fumarates or maleates can also produce polymers with similar structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similar phenomenon can be observed when pyrene‐based compound is added in the mixture of its solvent and non‐solvent with suitable fraction, which can force the aggregation of compounds and give a hand to the formation of pyrene excimers , . The formation of pyrene excimers will be influenced by lots of factors, such as the concentration of pyrene molecules in the system, the interaction between the pyrene fluorogens, the steric configuration of the pyrene‐based molecules and so on , . Lots of pyrene‐based fluorescent probes have been reported to be used in the response to heavy metals, temperature and so on based on their excimer fluorescent property,, so it maybe a feasible way for combining antimony reactive functional group with pyrene core to design pyrene‐basd antimony probes, which can change the speed for the formation of pyrene excimers in the system, and achieve the fluorescent detection of antimony with high sensitivity.…”
Section: Introductionmentioning
confidence: 71%
“…For pyrene excimers, it has been demonstrated that the chain lengths of end-to-end Py-labeled polymers, or the spatial spacing between successive pyrene moieties, exhibited a dramatic effect on the probability of an encounter between an excited pyrene and a ground-state pyrene. 28,29 Therefore, in turn, the differences in statistical sequences were directly reflected by the regularly changing I E /I M ratios for pyrene moieties.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%